Agências de promoç\~ao de investimento: Papel, funç\~oes, atividades e definiç\~ao de estratégias - Edmundo Inacio Junior; Cássio Garcia Ribeiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Policies aimed at favoring the attraction of FDI have been gaining strength on the agenda of national governments, largely supported by the so-called Investment Promotion Agencies (APIs). The purpose of this Discussion paper is to analyze the list of instruments adopted by such agencies. The methodology used in this research is based on bibliographic research, documentary research and analysis of secondary data. Based on the present study, it is possible to state that the range of mechanisms adopted by the APIs are not restricted to services that occur during the stages of definition and establishment of FDI projects, such as promoting visits to the place where the investment will take place and the promotion of working meetings with local stakeholders. This range also includes the provision of additional assistance, already after the implementation of MNCs in that location, in order to favor the decisions of expansions and reinvest ments made by such companies, such as the availability of a database of local suppliers and ombudsman services. This study also indicates the importance of APIs engaging in the creation and permanent review of strategic planning. Such document assumes the function of subsidizing the elaboration of the instruments of attraction and retention of FDI to be adopted by the Agencies. In addition, this Text for Discussion indicates the importance of the process of evaluating the policies practiced by the APIs, with a view to ascertaining the effectiveness of these policies, in addition to indicating the need for any adjustments, changes in priorities, as well as the range of instruments used.
Keywords: F21; G28; 330; investment; ombudsman; foreign; agency